Technico-economical analysis of a hybrid wave power-air compression storage system. (February 2015) - Hernández-Torres, David; Bridier, Laurent; David, Mathieu; Lauret, Philippe; Ardiale, Thomas
Abstract: This paper presents a technico-economical analysis of a Pelamis wave power generator coupled with a proposed air compression storage system. Ocean wave measurements and forecasts are used from a site near the city of Saint-Pierre in Réunion island, France. The insular context requires both smoothing and forecast of the output power from the wave power system. The storage system is a solution to meet this requirement. Several power network services are defined by the utility operator in order to meet different load needs. The goal is to analyze the role of the proposed storage device for each desired network service. An optimization procedure, from previous works, based on available wave energy forecast, is used to compute the optimal storage size for each service. An economical analysis shows the feasibility from the addition of the storage device, as the hybrid source power output may be economically profitable compared to a raw wave power production. Highlights: A novel subject is presented: wave power source with air compressor storage system. A solution to island power system renewable energy integration is proposed. A new charge/discharge methodology is studied for the storage device. The management method is designed for real-time operational conditions. The analysis complies with current regulations from the utility operator.